Percutaneous treatment of left side cardiac valves : A practical guide for the interventional cardiologist - Tamburino, Corrado (Springer Milan, 2012)
Transcatheter aortic valve implantation and percutaneous mitral valve repair have now been demonstrated to be credible alternatives to surgery in high-risk patients. The interest in these techniques is such that further significant technological changes are expected over the next few years. This revolution is already underway, rendering much prior knowledge obsolete. The success of the first edition of Percutaneous Treatment of Left Side Cardiac Valves has convinced us of the need to update the book in order to keep pace with the rapid and dynamic evolution in the discipline. Once again, this practical guide is designed to provide the reader with complete state of the art information on the techniques and approaches to percutaneous treatment of left side cardiac valve disease. Numerous images will help the reader to understand in detail the steps of each procedure. The potential complications and expected or potential morbidity from each procedure are discussed in depth, and the best ways to manage them are carefully explained. The book is also intended as a reference covering the up-to-date knowledge contained in the literature on the application of transcatheter techniques to cardiac valves.